Bilateral Oophorectomy and Breast Cancer Risk in BRCA1 and BRCA2 Mutation Carriers. (6th September 2016) - Kotsopoulos, Joanne; Huzarski, Tomasz; Gronwald, Jacek; Singer, Christian F; Moller, Pal; Lynch, Henry T; Armel, Susan; Karlan, Beth; Foulkes, William D; Neuhausen, Susan L; Senter, Leigha; Tung, Nadine; et al.
Abstract : Background: Whether oophorectomy reduces breast cancer risk among BRCA mutation carriers is a matter of debate. We undertook a prospective analysis of bilateral oophorectomy and breast cancer risk in BRCA mutation carriers. Methods: Subjects had no history of cancer, had both breasts intact, and had information on oophorectomy status (n = 3722). Women were followed until breast cancer diagnosis, prophylactic bilateral mastectomy, or death. A Cox regression model was used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs) of breast cancer associated with oophorectomy (coded as a time-dependent variable). All statistical tests were two-sided. Results: Over a mean follow-up of 5.6 years, 350 new breast cancers were diagnosed. Among women with a BRCA1 or BRCA2 mutation, oophorectomy was not associated with breast cancer risk compared with women who did not undergo an oophorectomy. The age-adjusted hazard ratio associated with oophorectomy was 0.96 (95% CI = 0.73 to 1.26, P = .76) for BRCA1 and was 0.65 (95% CI = 0.37 to 1.16, P = .14) for BRCA2 mutation carriers. In stratified analyses, the effect of oophorectomy was statistically significant for breast cancer in BRCA2 mutation carriers diagnosed prior to age 50 years (age-adjusted HR = 0.18, 95% CI = 0.05 to 0.63, P = .007). Oophorectomy was not associated with risk of breast cancer prior to age 50 years among BRCA1 mutation carriers (age-adjusted HR = 0.79, 95% CI = 0.55 to 1.13, P = .51). Conclusions: Findings from this large prospective study support a role of oophorectomy for the prevention of premenopausal breast cancer in BRCA2, but not BRCA1 mutation carriers. These findings warrant further evaluation.